SAAL: catálogo do requisito não funcional de segurança para ambientes de vida assistida - Guerra, Camila Stéfany Diógenes (2024)
In recent years, the demand for the development of systems focused on Ambient Assisted Living (AAL) has grown significantly. These intelligent environments aim to support the daily activities of elderly individuals, people with chronic conditions, or those with disabilities. Due to their critical nature, Requirements Engineering (RE) plays an essential role in developing the involved assistive technologies, especially concerning the Non-Functional Requirement (NFR) of security, where the protection of sensitive data and critical infrastructures is crucial. Thus, this work involves the creation of a specific catalog for the NFR of security in AAL systems. The catalog aims to assist software engineers in eliciting and specifying security-related requirements. To achieve this, a consolidated approach for cataloging NFRs was adopted, utilizing established research methods such as Snowballing and Grounded Theory. The proposed catalog was validated through interviews and questionnaires with area specialists to gain insights from the knowledge of software engineers and developers. The main contribution of this work is the development of a catalog based on the structured model of the Softgoal Interdependency Graph (SIG) focused on the security NFR. The catalog consists of two categories, ten subcharacteristics, and fifty-five recommendations for solutions and development strategies related to security in AAL systems. Thus, software engineers and developers can, when modeling this requirement, identify patterns, understand its subcharacteristics, and apply the best-known solutions and development strategies.